FE based mode interaction analysis of thin-walled steel box columns under axial compression - Kıymaz, Güven (ELSEVIER SCI LTD, THE BOULEVARD, LANGFORD LANE, KIDLINGTON, OXFORD OX5 1GB, OXON, ENGLAND, 2005)
This paper presents the Finite Element (FE) analysis based mode interaction analysis of thin-walled steel box columns under axial compression. Earlier theoretical results on the optimum design of axially compressed box columns were validated through FE analysis. The study was then extended to cover factors that were previously omitted. These factors included column out-of-straightness, residual stresses and plasticity. Emphasis was given on imperfection sensitivity and its effect on optimum design. (C) 2005 Elsevier Ltd. All rights reserved.
Keywords: thin-walled steel box columns; interaction column buckling; finite element analysis; ince duvarlı çelik kutu sütunları; etkileşim kolonunda burkulma; sonlu elemanlar analizi